Dynamic cities and creative clusters - Wu, Weiping (Policy research working paper, 2005)
"Wu focuses on how urban policies and the clustering of creative industries has influenced urban outcomes. The set of creative industries include those with output protectable under some form of intellectual property law. More specifically, this subsector encompasses software, multimedia, video games, industrial design, fashion, publishing, and research and development. The cities that form the basis for the empirical investigations are those where policy-induced transitions have been most evident, including Boston; San Francisco; San Diego; Seattle; Austin; Washington, D.C.; Dublin (Ireland); Hong Kong (China); and Bangalore (India). The key research questions are: What types of cities are creative? What locational factors are essential? What are the common urban policy initiatives used by creative cities? The author explores the importance of the external environment for innovation and places it in the larger context of national innovation systems. Based on a study of development in Boston and San Diego, he isolates the factors and policies that have contributed to the local clustering of particular creative industries. In both cities, universities have played a major role in catalyzing the local economy by generating cutting-edge research findings, proactively collaborating with industries, and supplying the needed human capital. In addition, these two cities benefited from the existence of anchor firms and active industry associations that promoted fruitful university-industry links. Many cities in East Asia are aspiring to become the creative hubs of the region. But their investments tend to be heavily biased toward infrastructure provision. Although this is necessary, the heavy emphasis on hardware can lead to underinvestment in developing the talents and skills needed for the emergence of creative industries in these cities.